Microfluidic metamaterial sensor: Selective trapping and remote sensing of microparticles - Shih, Kailing (2017)
We experimentally demonstrate the integration of a microfluidic trap array on top of metamaterial resonators for size selective trapping and remote sensing of microparticles. A split-ring resonator (SRR) design supports strongly confined electric field in the capacitive split gap at the fundamental inductive-capacitive resonance mode. The tightly confined electric field in the SRR gap forms a hot-spot that has become an enabling platform for sensing applications. Here, we extend the concept of metamaterial sensing to “trapping and sensing” by fabricating trapezoidal shaped structures near the split gap that enables trapping of microparticles in the split-gap region of each SRR. The proposed microfluidic metamaterial sensor enables sensing of different refractive index microparticles in terms of change in the transmitted amplitude and resonance frequency of the fundamental resonance mode operating in the terahertz spectral region. The proposed approach exploits the advantages offered by microfluidics, metamaterials, and terahertz technologies to form an ideal platform for ultra-sensitive, label-free, remote, and non-destructive detection of micro-substances.